Growth Impairment and Nutritional Deficiencies in a Cow's Milk-Allergic Infant Fed by Unmodified Donkey's Milk - Enza D'Auria; Marzia Mandelli; Patrizia Ballista; Francesco Di Dio; Marcello Giovannini (Case Reports in Pediatrics)
We report a case of growth impairment and nutritional deficiencies in a five-month infant fed by unmodified donkey's milk. We discuss the energy and macronutrient daily intake from donkey's milk and the nutritional consequences that can occur if this kind of milk is used unmodified in the first year of life.